Influential Article Review- How Ownership Structure Affects Innovation and Research and Development - Bush, Cathy; Chandler, Janis; Gilbert, Ada (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation and ownership. We present insights from a highly influential paper. Here are the highlights from this paper: This paper examines the effects of ownership types on firms’ R&D intensity and innovation performance, using a sample of 357,857 Chinese firms from 2005 to 2007. This study finds considerable divergence among Chinese domestic enterprises in terms of R&D intensity and innovation performance. We find that firms owned by the central government are the key drivers for firms’ R&D activities, while local government, private and foreign ownerships are negatively related to both R&D intensity and innovation performance. This paper finds significant divergence within government ownership category and argues that China’s institutional changes generate varied government ownership groups with different levels of resource endowment, which in turn influence firms’ R&D activities. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.